Hydroxyapatite-Functionalized Graphene: A New Hybrid Nanomaterial. (20th July 2014) - Rodríguez-González, C.; Cid-Luna, H. E.; Salas, P.; Castaño, V. M.
Abstract : Graphene oxide sheets (GO) were functionalized with hydroxyapatite nanoparticles (nHAp) through a simple and effective hydrothermal treatment and a novel physicochemical process. Microstructure and crystallinity were investigated by Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, X-ray diffraction (XRD), ultraviolet-visible (UV-Vis) absorption spectroscopy, and thermogravimetric analysis (TGA). Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were performed to characterize the morphology of the functionalized material. The resulting novel materials combine the biocompatibility of the nHAp with the strength and physical properties of the graphene.